Interest rates and inflation: What are the links? - Malcolm Sawyer (Intervention. European Journal of Economics and Economic Policies, 2009)
The purpose is to examine some of the links in the chain which is said to run from the rate of interest to the rate of inflation. It is argued that that there is a tendency to slip from arguments which that the rate of interest is related to the price level to suggesting that the rate of interest is related to the rate of inflation. The neo-Wicksellian approach is examined and found to support more the view that the rate of interest impacts the level of prices rather than the rate of inflation. It is also argued that the route through the exchange rate does not support the view that higher interest rates will dampen down inflation (though it may lower prices relative to what they would have been). It is further argued that the link from the level of economic activity to the rate of infl ation is theoretically dubious. In the last section it is briefly indicated that there is a lack of empirical support for any strong link from interest rate to inflation.
Keywords: E31; E40; E43; E52; 330; interest rates; inflation; monetary policy